2015
DOI: 10.1007/s00467-015-3090-x
|View full text |Cite
|
Sign up to set email alerts
|

Renal function can be impaired in children with primary hyperoxaluria type 3

Abstract: We found that the GFR was significantly impaired in two of our seven patients with PH3 diagnosed during childhood. This finding is in contrast to the early-impaired renal function in PH1 and PH2 and appears to refute to preliminary reassuring data on renal function in PH3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 17 publications
3
34
4
Order By: Relevance
“…This is in contrast to the previous data reporting a favorable outcome in PH3 . However, our results were similar to the study of Allard et al , where reported two patient experienced impaired glomerular filtration rates (GFR), with chronic kidney disease (CKD) stage 2 occurring early during childhood in a three several affected patients in the context of a homozygous HOGA1 mutation (p.Pro190Leu) together with a heterozygous AGXT mutation (p.Asp201Glu) . Thus, demonstrating the triallelic inheritance, defined as the presence of a disease‐modulating heterozygous AGXT mutation.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This is in contrast to the previous data reporting a favorable outcome in PH3 . However, our results were similar to the study of Allard et al , where reported two patient experienced impaired glomerular filtration rates (GFR), with chronic kidney disease (CKD) stage 2 occurring early during childhood in a three several affected patients in the context of a homozygous HOGA1 mutation (p.Pro190Leu) together with a heterozygous AGXT mutation (p.Asp201Glu) . Thus, demonstrating the triallelic inheritance, defined as the presence of a disease‐modulating heterozygous AGXT mutation.…”
Section: Discussionsupporting
confidence: 85%
“…The p.Gly287Val was found in most reported studies in the heterozygous state and in one case reported recently in homozygous state . The p.Gly287Val mutation has been identified in five Ashkenazi Jewish PH3 probands and in a Caucasian patient . The p.Gly287Val mutation was associated with the c.469‐31T>C polymorphism in intron 6, reported with a frequency equal to 0.07 in GMAF.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…PH3 (MIM #613616) is caused by mutations in the HOGA1 gene (MIM*613597), that encodes the mitochondrial enzyme 4-hydroxy-2-oxoglutarate aldolase (HOGA), catalysing the final step of 4-hydroxy-2-oxoglutarate catabolism to glyoxylate and pyruvate [9]. The age at onset of signs and symptoms is similar to those of PH1 and PH2, but in most PH3 patients a clinical remission is observed in the adult, despite the persistence of high oxalemia and oxaluria levels [10,11].…”
Section: Introductionmentioning
confidence: 89%